Analysis of factors affecting the accuracy of colposcopic diagnosis of cervical lesions: a retrospective cohort study - Chu, Yuqing; Chen, Qi; Liu, Ruixue; Zhou, Xu; Bao, Meijing; Wang, Hong; Lin, Yang (Frontiers in Medicine, 2024)
Background Cervical cancer is a leading cause of cancer-related deaths among women. However, in developing countries, the primary focus for cervical cancer prevention and control remains on the timely detection and treatment of precancerous lesions. This study aims to evaluate the accuracy of colposcopic diagnosis of cervical intraepithelial lesions and analyze the factors influencing its accuracy. Methods This study collected data from 512 eligible patients who visited the gynecology outpatient clinic of the Second Hospital of Jilin University from January 2022 to August 2023. The final diagnosis was based on the highest grade observed in both biopsy pathology and postoperative pathology. A self-controlled, retrospective analysis was conducted to evaluate the accuracy of colposcopic diagnosis. Univariate analysis was used to assess the impact of factors such as menopausal status, duration of menopause, high-risk human papillomavirus (HR-HPV) genotypes, and transformation zone (TZ) types on the accuracy of colposcopic diagnosis of cervical lesions. Result The overall colposcopy diagnostic concordance rate was 78.71%. The concordance rates between the premenopausal and postmenopausal groups differed significantly (χ2 = 75.450, p < 0.05). The HPV16/18 positive group and the non 16/18 HR-HPV positive group also showed a significant difference in concordance rates (χ2 = 5.890, p < 0.05). There were significant differences in concordance rates between TZ2 and TZ3 (χ2 = 10.585, p < 0.05), as well as between TZ1 and TZ3 (χ2 = 14.607, p < 0.05). Conclusion Factors such as menopausal status, duration of menopause, HR-HPV genotypes, and TZ types influence the accuracy of colposcopic diagnosis. Therefore, a comprehensive evaluation incorporating these factors should be performed in clinical practice to enhance diagnostic accuracy.